2015
DOI: 10.1155/2015/956082
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of IL‐1β, IL‐6, TGF‐β, and MMP‐9 in Patients Undergoing Carotid Artery Stenting and Regulation of MMP‐9 in a New In Vitro Model of THP‐1 Cells Activated by Stenting

Abstract: Inflammation plays an important role in the pathophysiological process after carotid artery stenting (CAS). Monocyte is a significant source of inflammatory cytokines in vascular remodeling. Telmisartan could reduce inflammation. In our study, we first found that, after CAS, the serum IL-1β, IL-6, TGF-β, and MMP-9 levels were significantly increased, but only MMP-9 level was elevated no less than 3 months. Second, we established a new in vitro model, where THP-1 monocytes were treated with the supernatants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 67 publications
1
16
0
1
Order By: Relevance
“…The inhibitory effects of TLM on A-FABP [64, 65] and monocytic cell adhesions [66] may have been mediated by PPARƔ activation; and on MMP-9 [6772] by Elk-1 phosphorylation inhibition [67]. While TLM was previously shown to lower cholesterol [73, 74], possibly through inhibiting intestinal cholesterol absorption [74], such reduction was not seen in the current study.…”
Section: Discussionmentioning
confidence: 60%
“…The inhibitory effects of TLM on A-FABP [64, 65] and monocytic cell adhesions [66] may have been mediated by PPARƔ activation; and on MMP-9 [6772] by Elk-1 phosphorylation inhibition [67]. While TLM was previously shown to lower cholesterol [73, 74], possibly through inhibiting intestinal cholesterol absorption [74], such reduction was not seen in the current study.…”
Section: Discussionmentioning
confidence: 60%
“…The treatment of acute ischemic stroke (AIS) is a very complicated process, but the effect of Western medicine treatment is not satisfactory (Xu & Li, 2011). It has been proven that the traditional Chinese medicine can play the advantage of treating both root causes and symptoms of inflammatory response in AIS patients with endovascular intervention examination (Zhang et al, 2015). It has been proven that the traditional Chinese medicine can play the advantage of treating both root causes and symptoms of inflammatory response in AIS patients with endovascular intervention examination (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional Chinese medicine has been used in vascular disease treatment for thousands of years in the Asia-Pacific region. It has been proven that the traditional Chinese medicine can play the advantage of treating both root causes and symptoms of inflammatory response in AIS patients with endovascular intervention examination (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of MMP-9 and/or TIMP in CS patients subjected to stenting (CAS) or endarterectomy (CEA) Zhang et al conducted an extensive study to verify an association between serum level of MMP-9 and the stenting procedure. In this study, concentrations of MMP-9 were assessed prior to the procedure, 24 h, 3-and 6-month thereafter [16]. Elevated levels of MMP-9 were observed for at least 3 months post-procedure, which suggested that this metalloproteinase may be involved in the process of in-stent stenosis.…”
Section: 5mentioning
confidence: 94%
“…Analyse of MMP-9 level in patients with symptomatic CS treated by stenting (n = 57) showed elevated levels of MMP-9 not only 24 h post-stenting but also up to 30 days thereafter; concentrations of MMP-9 determined prior to the stenting, 24 h and 30 days post-procedure amounted to 100 pg/ml, 125 pg/ml and 118 pg/ml, respectively (Setacci et al similar to Zhang et al). Carotid stenting was associated with two TIA episodes directly after the procedure, two TIA episode and death within a month after the discharge from the hospital [16,17].…”
Section: 5mentioning
confidence: 99%